Health information networking via the Internet with the former Soviet Union. - Teplitskaia, H (1997)
Because of the severe financial hardships associated with the transition to a market economy in the Newly Independent States (NIS) of the former Soviet Union, the Internet has become a major link to health care resources for many health care workers. In 1992, the University of Illinois at Chicago Library of the Health Sciences (UIC LHS) initiated a special support project with goals of enhancing access to international biomedical information and facilitating international professional networking for interested NIS organizations and individuals. Project objectives included an information needs assessment, development of culturally sensitive Internet training applications, information and referral services, and follow-up e-mail consultations for NIS participants. This paper reviews the historical context of the health care partnerships between the United States and the NIS, and of the UIC LHS International Health Information Networking Project. In the context of UIC, international networking cross-cultural observations, teaching techniques, a Russian training experience, and the development of a Web-based course are reported.